Preponed Budburst in Grapevine ‘Cabernet Sauvignon’ Enables Berry Harvest before Monsoon in Lower Hills of Nepal - Sapkota, Puja; Ghimire, Nishes; Sapkota, Rekha; Poudel, Pragya; Dahal, Kishor Chandra (Nepalese Horticulture, 2024)
Berry harvesting coinciding with the monsoon is the major problem of grapevine (Vitis vinifera L.) cultivation in Nepal. Nepalese viticulture is benefitted by advancing budburst and hydrogen cyanamide (HC) has the potential to break the bud dormancy in grapevine leading to early harvesting. To prepone the budburst and thus the harvesting, field experiment was conducted in a commercial vineyard, Dhading, aiming to identify the appropriate dose of HC for the advancement of natural budburst in cv. Cabernet Sauvignon. Six HC application treatments; (i) Control, ii) 2% HC, iii) 3.5% HC, iv) 5% HC, v) 6.5% HC, and vi) 8% HC) were replicated four times considering vine as replication in randomized complete block design. Grapevine growth were recorded using a modified Eichhorn and Lorenz (E-L) growth stage notation, and other quantitative and qualitative attributes were measured at flowering and harvesting. HC preponed the budburst (about 3 weeks) compared to control. Number of days to 50% budburst was earlier (31 days) in 3.5% HC treated vines than in control. Budburst and flowering were maximum (70±2.72% and 63.33±4.08%, respectively) in 2% HC treated vines and the lowest (20.83±14.17% and 19.17±13.63%, respectively) was in 8% HC treated vines in 84 days after HC application. TSS was varied but the average bunch weight did not differ with HC treatments in the same day of harvest. Higher HC concentration (≥6.5%) adversely affected the budburst and thus in flowering and yield. The HC was effective to prepone the natural budburst calendar, shoot growth and flowering, enabling harvesting before monsoon. The HC 2% application in winter buds was found appropriate for the cv. Cabernet Sauvignon to prepone budburst and harvesting before monsoon. The HC dose and application timing might be differ in cultivars and growing condition, thus, cultivar and location specific researches are recommended